Pelatihan Pembuatan Pesawat OHLG untuk Pengembangan Spot Dirgantara di Destinasi Wisata Stone Park - Nurdin, Riani; Mauidzoh, Uyuunul; Prattiwi, Elisabeth Anna; Ahmadi, Nurfi; Gunawan, Gunawan; Astuti, Marni; Zabidi, Yasrin (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
Stone Park is one of the tourist destinations located in Turunan, Girisuko, Panggang, Gunungkidul. The Stone Park tourist destination is currently not widely visited by tourists because it only offers sunrise spot facilities, photo spots, gazebos, and camping areas that have been widely offered by other tourist destinations. To support Sustainable Tourism which can have a long-term impact on the environment, social, culture, and economy, it is necessary to develop attraction spots. The aerosport attraction spot is one of the attraction spots that is quite popular with the public. To provide understanding and skills, training has been held on making and flying the Out Hand Launch Glider (OHLG) Aircraft which was attended by 21 participants consisting of Stone Park tourist destination managers and the surrounding community. The participants were able to understand the need for the development of aerospace attraction spots and succeeded in making and flying the OHLG aircraft.